Ready-to-use violence prevention skills : lessons and activities for elementary students (The Center, 1999)
Life skills: coping with difficulties in life; learning to value life; understanding how to conquer fear; managing anger... Relationships: selecting trusted role models; learning to find acceptance without coercion... Family: learning the importance of rules; achieving family harmony... Stress and danger: understanding early signs of troublesome situations...